2014
DOI: 10.1002/humu.22707
|View full text |Cite
|
Sign up to set email alerts
|

Next Generation Sequencing Identifies a Novel Rearrangement in theHBBCluster Permitting to-the-Base Characterization

Abstract: Genetic testing for hemoglobinopathies is required for prenatal diagnosis, understanding complex cases where multiple pathogenic variants may be present or investigating cases of unexplained anemia. Characterization of disease causing variants that range from single base changes to large rearrangements may require several different labor-intensive methodologies. Multiplex ligation probe amplification analysis is the current method used to detect indels, but the technique does not characterize the breakpoints o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 29 publications
0
21
0
Order By: Relevance
“…Another mechanism of increasing α globin output is through segmental duplication of the whole α globin complex (Harteveld et al , ) but breakpoints of the reported duplications have not been fully characterised due to technological limitations. Here, we applied a previously described next generation sequencing (NGS) methodology (Shooter et al , ,b) to characterise three α globin cluster duplications, permitting to‐the‐base resolution in two of the three cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Another mechanism of increasing α globin output is through segmental duplication of the whole α globin complex (Harteveld et al , ) but breakpoints of the reported duplications have not been fully characterised due to technological limitations. Here, we applied a previously described next generation sequencing (NGS) methodology (Shooter et al , ,b) to characterise three α globin cluster duplications, permitting to‐the‐base resolution in two of the three cases.…”
mentioning
confidence: 99%
“…Genomic DNA was extracted using the Qiagen Symphony whole blood midi kit and eluted into 200 μl ATE buffer. NGS was performed as previously described (Shooter et al , ). DNA (5 μg) was sheared using a Covaris E220 to a mean size of 500 bp and purified by double size selection using Agencourt SPRIselect beads (Beckman Coulter, Brea, CA, USA).…”
mentioning
confidence: 99%
“…Normal and positive controls with known genetic rearrangements were analysed in parallel with the test samples. All data analyses were carried out using NextGene (SoftGenetics, State College, PA, USA) as described (Shooter et al , ). A normalized measure of the coverage across the sequenced region, known as repeats per kilobase exon model per million mapped reads (RPKM), was calculated for each 120 bp region covered in the in‐solution bait capture.…”
mentioning
confidence: 54%
“…A next generation sequencing (NGS) assay and bioinformatic strategy was used to identify any potential rearrangement in the HBA and HBB globin gene loci that could explain the unusually low HbS (Shooter et al , ). Leucocyte‐extracted DNA (3 μg) was sheared to 500 bp using a Bioruptor (Diagenode, Denville, NJ, USA) and used to construct a sequencing library with minimal polymerase chain reaction (PCR) amplification.…”
mentioning
confidence: 99%
“…Several studies indicated that the BCL11A, HMIP, and β-globin regions were associated with increased HbF levels in different populations; and investigation of these genotypes with respect to pain crisis is warranted in different population, which may help in prognostication, as also a genome-wide association study, which may help uncover new loci controlling HbF levels [14] [15].…”
Section: Introductionmentioning
confidence: 99%